Parametric study of quarter-wave resonators for sound-proofing building structures - Idrissi Majid; Lemkalli Brahim; Mir Abdellah; Bouzid Abdenbi; Achaoui Younes (E3S Web of Conferences)
This study investigates the parametric analysis of a quarter-wave resonator integrated into a brick structure for optimized acoustic isolation in buildings. Starting with a brick of 100 mm thickness and period, the quarter-wave resonator was designed and parametrized. The optimization process yielded significant results, achieving an attenuation of approximately -87 dB with a bandgap width of 82%, surpassing the -72.55 dB attenuation provided by the mass law of the brick alone. These findings highlight the potential of the optimized resonator structure to enhance acoustic isolation, making it a promising solution for noise control in urban environments.